Anne of Green Gables - Young Readers' Classics - L. M. Montgomery (Key Porter Books Ltd Toronto, Canada, 1993)
Anne, an eleven-year-old orphan, is sent by mistake to live with a lonely, middle-aged brother and sister on a Prince Edward Island farm and proceeds to make an indelible impression on everyone around her.
Keywords: Classics -- Classics